2010
DOI: 10.2353/ajpath.2010.080639
|View full text |Cite
|
Sign up to set email alerts
|

Enoxaparin Improves the Course of Dextran Sodium Sulfate-Induced Colitis in Syndecan-1-Deficient Mice

Abstract: Syndecan-1 (Sdc1) plays a major role in wound healing and modulates inflammatory responses. Sdc1 expression is reduced in lesions of patients with ulcerative colitis. The aim of this study was to investigate the role of Sdc1 in murine dextran sodium sulfate (DSS)-induced colitis. DSS colitis was induced in Sdc1-deficient (knockout (KO)) and wild-type mice by oral administration of 3% DSS. KO mice exhibited a significantly increased lethality as compared with wild-type controls (61 versus 5% , P < 0.05). Impair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 46 publications
4
67
0
Order By: Relevance
“…It is reported that apart from its anticoagulant effect, low-molecular-weight heparin is also characterized by its anti-inflammatory effect, which has been confirmed in human diseases and animal inflammatory models [25], and dysfunction of immune reaction resulting from T-cell activation disturbance is a common feature of the animals in these inflammatory models. The exact anti-inflammatory mechanisms of heparin have not yet been found.…”
Section: Introductionmentioning
confidence: 98%
“…It is reported that apart from its anticoagulant effect, low-molecular-weight heparin is also characterized by its anti-inflammatory effect, which has been confirmed in human diseases and animal inflammatory models [25], and dysfunction of immune reaction resulting from T-cell activation disturbance is a common feature of the animals in these inflammatory models. The exact anti-inflammatory mechanisms of heparin have not yet been found.…”
Section: Introductionmentioning
confidence: 98%
“…Although syndecan-1 knockout (Sdc-1 2/2 ) mice show exacerbated disease symptoms in several inflammatory models (14), precisely why this is the case remains unclear. Most studies report enhanced immune cell infiltration in Sdc-1 2/2 mice, which has been correlated with enhanced extravasation from postcapillary venules because of effects ranging from modulation of integrin activity and interaction with cell adhesion molecules (14,15) to modulation of cytokine and chemokine gradients (16). Yet, the expression of syndecan-1 on endothelium and immune cells in vivo is difficult to detect, with the notable exception of B lymphocytes, which may be partially because of its dynamic regulation (9,(17)(18)(19).…”
mentioning
confidence: 99%
“…Adhesion Assays-bEnd.3 cells were used for static lymphocyte adhesion assays, as described previously (26,49). Approximately 2 ϫ 10 4 endothelial cells/well were cultured in 96-well plates overnight, followed by treatment with 85 g/ml TNF-␣ to stimulate endothelial cells.…”
Section: Methodsmentioning
confidence: 99%